"Discipline that hurts": Punitive logics and governance in sport. (December 2020) - Kennedy, Liam; Silva, Derek
In this paper, we undertake a case study of the National Hockey League's supplementary discipline regime to reflect on the ways in which discourses about social harm are configured, taken up and used in the sporting landscape and how they reflect and reify narrow understandings of crime and punishment. We find that the hockey world employs predictable crime and justice metaphors when discussing on-ice violence and suggest this breeds fear and legitimates governance strategies. The National Hockey League's supplemental discipline process itself—much like penality away from the rink—is characterized by multiple, sometimes contradictory, objectives. Notably, the league responsibilizes players, long endorsing or accepting vigilantism, refusing to enact structural changes, and compelling players themselves to create a safe workplace. This regime has contributed to financial struggles, chronic physical and mental health issues, and the early deaths of a host of former players.